The Role of Corona Anxiety on Mental Health and Quality of Life Mediated by Hope - mansooreh nikoogoftar; mahtab dousti (پژوهشنامه روانشناسی مثبت, 2021)
The coronavirus has had a far-reaching impact on human beings' economic, social, communication, environmental, and personal dimensions. An accurate understanding of these broad implications and planning appropriate interventions requires interdisciplinary studies. Therefore, this study was conducted to investigate the psychological effects of coronavirus and psychological protective factors against the damage caused by it. In addition, this study aimed to examine the effect of corona anxiety on mental health and quality of life mediated by hope in the general population. The research method was descriptive-correlation, and structural equation modeling was used to test the relationships between variables. The coronavirus has had a far-reaching impact on human beings' economic, social,communication, environmental, and personal dimensions. An available sampling method selected an accurate understanding of these broad effects and 230 cyberspace users. The instruments used in this study were the Corona Anxiety Scale, Mental Health Questionnaire, Quality of Life Questionnaire, and the Hope Scale. Findings showed that corona anxiety significantly affects mental health and quality of life, and hope positively affects mental health and quality of life. The mediating role of hope in the effect of corona anxiety on mental health and quality of life was also significant. Therefore, it can be concluded that hope can improve mental health and quality of life by reducing corona anxiety.